The Helmholtz Curves : Tracing Lost Time - Schmidgen, Henning (Book collections on Project MUSE., 2014)
This book reconstructs the emergence of the phenomenon of ""lost time"" by engaging with two of the most significant time experts of the nineteenth century: the German physiologist Hermann von Helmholtz and the French writer Marcel Proust. Its starting point is the archival discovery of curve images that Helmholtz produced in the context of pathbreaking experiments on the temporality of the nervous system in 1851. With a ""frog drawing machine, "" Helmholtz established the temporal gap between stimulus and response that has remained a core issue in debates between neuroscientists and philosophe.